ANALISIS OZON BERBASIS SATELIT AIRS NASA GIOVANNI SYSTEM - Mariati, Heny; Suryani, Novelisa; Afandi, Roky (Jurnal Spasial, 2019)
This study aims to study and analyze changes in ozone concentration and its influence with the phenomenon of forest fires in the Sumtra region and see the distribution of ozone concentrations according to latitude zones of the Sumatra region. With the observation method using AIRS satellite data and utilizing the Giovvani System web tool to calculate ozone concentrations every month from January-September. the results showed a significant decrease in stratospheric ozone concentrations in September following the increase in CO during severe forest fires. Abnormal circumstances occur where ozone concentrations decrease significantly in August and September, occurring with a concentration range of 19 to 26 DU from the highest average in May. The effect of forest and land fires is also condemned by the distribution of CO in September which increased by 119 ppbv compared to January to July CO concentrations ranged from 75 to 85 ppbv. A quite different pattern occurred in August and September where ozone concentrations decreased in zone 2 LS-2 LU which is a zone of forest fires in September.